(untitled) (Quinto Sol, 2023)
The following work analyzes the state intervention in tourism in Tucumán during the radical governments between 1935 and 1943, focusing especially on exploring the legislative debates around the 1936 tourism plan and on examining the functions, scope, and chronologies of the specialized departments of 1936 and 1942. Based on the widespread agreement that existed at the national level since the 1930s regarding the idea that tourism should be fostered and organized by the State, the article recovers the specifics of the Tucuman interventionist phenomenon. Thus, the foundations that allowed the establishment of a more active state role regarding tourism in Tucumán are investigated. For this, the marches and countermarches, the projects, regulations, debates, and capacities that defined certain types of agencies are problematized. Therefore, two core moments of the process of subnational state configuration at the tourism level are examined. To carry out this research, primary sources were used, such as session diaries of the parliamentary chambers of the province, written press of national and provincial rank, relevant State documentation such as descriptive memories, among others.